(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
The article examines the main tendencies in the transformation of national culture under the influence of globalization. It argues that globalization is not merely an economic or technological process, but also a complex socio-cultural phenomenon that changes everyday lifestyles, communication habits, value orientations and models of identity. The study pays particular attention to the tension between cultural standardization and the preservation of national uniqueness. On the one hand, global media, consumer culture and digital networks produce common behavioural patterns; on the other hand, national cultures continue to adapt, reinterpret and enrich global influences through local traditions, language, education and moral norms. The article concludes that the protection of national culture should not be understood as isolation from the world, but as a conscious strategy of cultural selectivity, spiritual resilience and responsible participation in global development